Penerapan Nilai Keislaman terhadap Kepuasan Nasabah di BMT NU Kota Kraksaan - Achmad Febrianto; Ferdiyansyah Ferdiyansyah (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The development of banking is seen from the efforts of bank services to customers in making institutions increasingly rapid, in increasing banking customers promoting rewards to make customers satisfied with bank services, the public is also still considering choosing a financial institution to be trusted in transactions in conventional or sharia financial institutions. The purpose of this study was to determine the application of Islamic values to customer satisfaction at BMT NU Kraksaan City. This study used a qualitative descriptive analysis approach. The results of this study from BMT NU in Kraksaan City in the application of existing Islamic values have won the trust of their customers. already very good from good service and using the basics of Islam adds more value.